African American Gerontology Network. - Ford, Marvella E.; Cochran, Donna L.; Neal, Earlene T. (Health & Social Work, 2000)
The writers discuss the work of the African American Gerontology Network (AAGN), which was formed to address feelings of isolation in the workplace among African-Americans in Michigan working in the field of gerontology. The origins of the AAGN and its mission and goals are outlined, and its membership, objectives, and organizational structure are noted. In addition, the AAGN's strengths, the challenges involved in forming and maintaining it, and its major accomplishments are noted. It is argued that as a unified group, members are able to maximize their collective resources, awareness, and knowledge. In addition, the AAGN also gives members a variety of options aimed at decreasing their feelings of isolation and enhancing their professional effectiveness. The organization's framework can be used as a model for aging professionals from ethnic minority groups in other states who want to increase their community partnerships and networks.